Intergovernmental Fiscal Instruments for Stimulating Regional Economic Growth in Russia - Igor Yu. Arlashkin (Финансовый журнал, 2020)
The article examines the instruments used in intergovernmental fiscal relations in order to promote economic growth of the regions of the Russian Federation. The task of stimulating regional economic growth is relevant in the need for the Strategy of Spatial Development of the Russian Federation until 2025 to be implemented. The article deals with various instruments of tax decentralization as well as three main types of fiscal transfers: “grants” (primarily equalization or balancing transfers), “subsidies” (earmarked co-funding transfers), and “other intergovernmental transfers” (other earmarked transfers). All these instruments are assessed from the standpoint of stimulating economic growth with special attention being paid to the tools used by regional governments to promote local economic growth. The article summarizes the results of the main econometric studies on the topic. As a result of the present study, it is shown that the main instruments for stimulating regional economic growth are earmarked transfers (primarily capital transfers) and decentralization of taxes on income (primarily corporate income tax). At the same time, since 2015 “other intergovernmental transfers” have been playing a more significant role in stimulating economic growth than “subsidies”, which is associated with an increase in the equalizing effect of the latter. Decentralization of property taxes has most likely not had a significant impact on regional economic growth, and the negative effect of equalizing transfers (“grants”) is smoothed out by special clauses built into the methodology for their distribution.